(untitled) (MEDICINE, PEDAGOGY AND TECHNOLOGY: THEORY AND PRACTICE, 2025)
Orthodontics, a vital branch of dentistry, has undergone significant advancements in recent decades with the development of modern methods for teeth alignment. Traditionally, fixed metal braces were the primary solution for correcting malocclusions and dental irregularities. However, innovations in materials science, digital technology, and biomechanics have introduced a wide range of effective, aesthetic, and patient-friendly alternatives.